2010
DOI: 10.1029/2009ja015242
|View full text |Cite
|
Sign up to set email alerts
|

First results on terrestrial gamma ray flashes from the Fermi Gamma‐ray Burst Monitor

Abstract: [1] The Gamma-ray Burst Monitor (GBM) on the Fermi Gamma-ray Space Telescope detected 12 intense terrestrial gamma ray flashes (TGFs) during its first year of observation. Typical maximum energies for most of the TGFs are ∼30 MeV, with one TGF having a 38 MeV photon; two of the TGFs are softer and longer than the others. After correcting for instrumental effects, a representative bright TGF is found to have a fluence of ∼0.7 photons cm −2 . Pulses are either symmetrical or have faster risetimes than fall times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
349
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 254 publications
(365 citation statements)
references
References 39 publications
12
349
0
4
Order By: Relevance
“…They were first observed in 1994 from the Compton Gamma‐ray Observatory satellite (Fishman et al, 1994) and later confirmed by other space‐based observations (Briggs et al, 2010; Marisaldi et al, 2010; Smith et al, 2005). X‐rays have also been observed at closer proximity to the source with sensors on the ground and on balloons (Dwyer, 2004; Mallick et al, 2012; Moore et al, 2001) and in high‐voltage laboratory discharge experiments of long sparks (Babich et al, 2015; Dwyer et al, 2005; Kochkin et al, 2014, 2016).…”
Section: Introductionmentioning
confidence: 68%
“…They were first observed in 1994 from the Compton Gamma‐ray Observatory satellite (Fishman et al, 1994) and later confirmed by other space‐based observations (Briggs et al, 2010; Marisaldi et al, 2010; Smith et al, 2005). X‐rays have also been observed at closer proximity to the source with sensors on the ground and on balloons (Dwyer, 2004; Mallick et al, 2012; Moore et al, 2001) and in high‐voltage laboratory discharge experiments of long sparks (Babich et al, 2015; Dwyer et al, 2005; Kochkin et al, 2014, 2016).…”
Section: Introductionmentioning
confidence: 68%
“…For years, thousands of TGFs have been detected by satellitebased experiments, such as AGILE [23] and GBM-Fermi [24]. The lightning initiation and correlations with thunderstorms have also been studied in details [16,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…[5] In addition to these direct, in situ observations of lightning in the ionosphere, recent measurements from satellites of terrestrial gamma radiation sources [e.g., Fishman et al, 1994;Smith et al, 2005;Briggs et al, 2010] have raised new interest in strong electric field coupling from lightning by demonstrating the influence of the lightning EMP on the upper atmosphere and ionosphere.…”
Section: Introductionmentioning
confidence: 99%